(+/-)-Licarin A and its semi-synthetic derivatives: In vitro and in silico evaluation of trypanocidal and schistosomicidal activities - Meleti, Vanderlisa Rita; Esperandim, Viviane Rodrigues; Bocalon Flauzino, Luzio Gabriel; Prizantelli, Anna Helena; Lima Paula, Lucas Antonio de; Magalhaes, Lizandra Guidi; Cunha, Wilson Roberto; Laurentiz, Rosangela da Silva [UNESP]; Rocha Pissurno, Ana Paula da [UNESP]; Dhammika Nanayakkara, N. P.; Pereira, Ana Carolina; Bastos, Jairo Kenupp; et al. (Elsevier B.V., 2020)
This paper reports the synthesis of (+/-)-licarin A 1, a dihydrobenzofuran neolignan, resultant of an oxidative coupling reaction of isoeugenol and horseradish peroxidase (HRP) enzyme. Following, three semi-synthetic derivatives from this compound were obtained: benzylated (+/-)-licarin A 2, methylated (+/-)-licarin A 3 and acetylated (+/-)-licarin A 4. After structural elucidation and assignment by Nuclear Magnetic Resonance of H-1, C-13 and DEPT, all compounds were evaluated in vitro against Trypomastigote forms of Trypanosoma cruzi (T. cruzi), the etiologic agent of Chagas disease, and Schistosoma mansoni (S. mansoni) worms, the etiologic agent of schistosomiasis. Compound (4) was the most active against S. mansoni adult worms, displaying worm viability reduction at 25 mu M and mortality of all worms at 100 and 200 mu M within 24 h. Compound 1 was the second most active, showing worm viability reduction at 50 mu M and mortality of 25% and 100% of worms in 24h at concentrations of 100 and 200 mu M, respectively. In addition, theoretical calculations aiming at finding molecular properties that showed the correlation for schistosomicidal and trypanocidal activities of (+/-)-licarin A and three of its semi-synthetic derivatives were also performed.
Keywords: (+/-)-Licarin A; Semi-synthetic derivatives; Trypanosoma cruzi; Schistosoma mansoni; computational study